A Slip Gap of the 2016 Mw 6.6 Muji, Xinjiang, China, Earthquake Inferred from Sentinel‐1 TOPS Interferometry - Feng, Wanpeng (2017)
We use Sentinel‐1A/1B Terrain Observation with Progressive Scans (TOPS) data to map coseismic and postseismic displacements for the 25 November 2016 Mw 6.6 Muji earthquake in southwestern Xinjiang, China. Two tracks (T27 and T107) of the TOPS data captured the coseismic deformation area with a maximum line‐of‐sight deformation of ∼0.25  m in the descending track (T107). The inverted best‐fitting coseismic slip model in this study shows that the mainshock was a right‐lateral strike‐slip rupture on the western segment of the Muji fault, with an optimal dip angle of 80°±4°. Two separated slip zones exist in the coseismic slip model, with the maximum slip of 1.6 m located in the western slip zone. The total geodetic moment is 9.87×1018  N·m, equivalent to an earthquake of Mw 6.6. Our model shows that a patch between the two slip zones remained unruptured during the mainshock, indicating a potential future seismic risk. Aftershocks recorded in the first 45 days after the mainshock delineate the modeled rupture patches well. The components of the regional Global Positioning System velocities parallel to the Muji fault have been inverted to obtain an interseismic slip rate of ∼10  mm/yr on this structure. The recent large strike‐slip earthquakes in this area, that is, the 2015 Mw 7.2 Tajikistan earthquake (left‐lateral) and 2016 Mw 6.6 Muji earthquake (right‐lateral), may be an indicator of conjugate fault systems at the west boundary between the Indian and Eurasian plates in response to north–south convergence produced by the collision of the two plates.